Studi Analisa Kebutuhan Jumlah Stasiun Hujan Berdasarkan Evaluasi Perbandingan Antara Analisa Hidrograf Banjir Dan Banjir Historis Pada Das Limboto Provinsi Gorontalo - Djafar, Haris; Limantara, Lily Montarcih; Asmaranto, Runi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
In the hydrologic analysis activities, the Errors in basic hydrological data monitoring in a drainage area of the river will result in data are not correct and lead to the result of planning and management of water resources is not efficient and effective. The errors are usually caused by a number of rainfall stations in the watershed inadequate and dispersal patterns of uneven rainfall stations. The purpose of this study is to obtain the results of the evaluation of the amount of rainfall stations WMO standards based on existing conditions, to determine the comparison between the design flood discharge KaganRodda method and the design flood discharge conditions using the existing station network, and to obtain recommendations amount and location of rainfall stations positions. This study conducted in watershed of Limboto, with an area of watershed is 902.91 km2 .The results of this study are recommending 16 rainfall stations where the 4 stations is the existing stations, with each station rainfall density is 8.038 km.Keywords: Flood, Kagan-rodda, Rain Station, Rain Station density.